2015
DOI: 10.5812/jjm.18102
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aminoglycoside Resistance Genes in Enterococcus and Salmonella Strains Isolated From Ilam and Milad Hospitals, Iran

Abstract: Background: Aminoglycosides are a group of antibiotics that have been widely used in the treatment of life-threatening infections of Gram-negative bacteria. Objectives: This study aimed to evaluate the frequency of aminoglycoside resistance genes in Enterococcus and Salmonella strains isolated from clinical samples by PCR. Materials and Methods: In this study, 140 and 79 isolates of Enterococcus and Salmonella were collected, respectively. After phenotypic biochemical confirmation, 117 and 77 isolates were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The first isolation of an armA -harboring Salmonella strain occurred in 2011; fortuitously, no increasing trend for armA presence was found in the community-acquired infections in Shanghai. As with other clinical Enterobacteriaceae isolates ( Samadi et al, 2015 ), the armA prevalence rate in clinical Salmonella isolates from the present work was found to remain low over the study period. However, the presence of other aminoglycoside-resistance genes was not assessed, and antimicrobial susceptibility testing was not performed on all the isolated strains from this study, only the strains with armA , so strains with other aminoglycoside resistance mechanisms may have remained undetected.…”
Section: Discussionsupporting
confidence: 70%
“…The first isolation of an armA -harboring Salmonella strain occurred in 2011; fortuitously, no increasing trend for armA presence was found in the community-acquired infections in Shanghai. As with other clinical Enterobacteriaceae isolates ( Samadi et al, 2015 ), the armA prevalence rate in clinical Salmonella isolates from the present work was found to remain low over the study period. However, the presence of other aminoglycoside-resistance genes was not assessed, and antimicrobial susceptibility testing was not performed on all the isolated strains from this study, only the strains with armA , so strains with other aminoglycoside resistance mechanisms may have remained undetected.…”
Section: Discussionsupporting
confidence: 70%
“…As well as, Stępień-Pyśniak et al in (2016) demonstrated that E. faecalis isolates absolute resistance 100% against erythromycin. Furthermore, Endo et al in (2014); Talebi et al in (2015); Samadi et al in (2015) and Pourcel et al in (2017) detected that 66.7% of isolates were resisting to azithromycin, 86% of isolates were resisting to tetracycline, 80% of isolates were resisting to amikacin and 77.2% of isolates were resisting to gentamicin, respectively;…”
Section: Antibiotics Susceptibility Testmentioning
confidence: 99%
“…Further, they showed that hMSCs differentiation toward chondrocytes was induced in the presence of higher concentrations of TGFβ-1 [92]. Polysaccharides derived from micro-organism sources have multiple industrial applications [93][94][95]. The advantages of this biomaterial include water-solubility, gelling capacity by lowering the temperature, and biological properties (such as non-cytotoxicity and cyto-compatibility) which make them suitable candidate for cartilage tissue engineering [96].…”
Section: Hyaluronanmentioning
confidence: 99%